Markets, Firms, and the Management of Labour in Modern Britain - Lewchuk, Wayne (Labour / Le Travail, 1993)
The article reviews the book,"Markets, Firms, and the Management of Labour in Modern Britain," by Howard F. Gospel.
Keywords: BOOKS -- Reviews; GOSPEL, Howard F.; MANPOWER; MARKETS, Firms & the Management of Labour in Modern Britain (Book); Nonfiction